Rancang Bangun Sistem Informasi Pencatatan Surat Izin dan Pelanggaran Siswa Berbasis Web di SMA Negeri 1 Pariaman - Salman, Afig Izaan; Huda, Yasdinul (TSAQOFAH, 2025)
Student administrative record-keeping, particularly regarding permission letters for class entry, early dismissal, and disciplinary violations is a critical component in maintaining an orderly and structured school environment. At SMAN 1 Pariaman, these records are still managed manually using logbooks, which pose significant risks of data loss or damage. This study aims to design and develop a web-based information system named SISPEL (Sistem Informasi Pencatatan Surat Izin dan Pelanggaran Siswa) to enhance the effectiveness, efficiency, and convenience of data management and monitoring. The system was developed using the waterfall model, encompassing stages of requirements analysis through observation, system design using UML, implementation with the Laravel framework for the backend and Bootstrap 5 for a responsive user interface, and data storage via MySQL. System testing was conducted using the Black Box Testing method, which confirmed that all functionalities from data management by administrators, data entry by operators, verification by vice principals, to monitoring by homeroom teachers functioned as intended and met the specified requirements. The system features a user-friendly interface and is accessible via both desktop and mobile devices. The findings indicate that SISPEL effectively addresses the inefficiencies of manual record-keeping, facilitates monitoring processes, minimizes data loss risks, and supports digital transformation in school administrative management.